Trait Hope and Preparation for Future Care Needs among Older Adult Primary Care Patients. Issue 2 (14th March 2016) - Southerland, Jodi L.; Slawson, Deborah L.; Pack, Robert; Sörensen, Silvia; Lyness, Jeffrey M.; Hirsch, Jameson K.
ABSTRACT: Objective : We examined associations between trait hope and preparation for future care needs (PFCN) among 66 older adult primary care patients in western New York. Methods : Participants completed a questionnaire assessing PFCN (awareness, information gathering, decision-making, concrete planning, and avoidance), and the Adult Trait Hope Scale. Results : In multivariate regressions, lower hope, particularly less agency, was associated with more awareness of needing care, whereas higher hopefulness, particularly pathways thinking, was associated with increased decision-making and concrete planning. Conclusions : Greater hopefulness appears to be linked to goal-directed planning behaviors, although those with lower hope may actually be more aware of the need for planning. Evidence-based programming that encourages learned hopefulness may contribute to enhanced health planning and decision-making among older adult primary care patients.